Flux eaudiobook A novel. - Chong, Jinwoo (Tantor Media, 2023)
A blazingly original and stylish debut novel about a young man whose reality unravels when he suspects his mysterious employers have inadvertently discovered time travel—and are using it to cover up a string of violent crimes . . . Four days before Christmas, eight-year-old Bo loses his mother in a tragic accident, twenty-eight-year-old Brandon loses his job after a hostile takeover of his big-media employer, and forty-eight-year-old Blue, a key witness in a criminal trial against an infamous now-defunct tech startup, struggles to reconnect with his family. So begins Jinwoo Chong's dazzling, time-bending debut that blends elements of neo-noir and speculative fiction as the lives of Bo, Brandon, and Blue begin to intersect, uncovering a network of secrets and an experimental technology that threatens to upend life itself. Intertwined with them is the saga of an iconic '80s detective show, Raider , whose star actor has imploded spectacularly after revelations of long-term, concealed abuse. Flux is a haunting and sometimes shocking exploration of the cyclical nature of grief, of moving past trauma, and of the pervasive nature of whiteness within the development of Asian identity in America.